MiR-384 Inhibits Malignant Biological Behavior Such as Proliferation and Invasion of Osteosarcoma by Regulating IGFBP3. (2nd March 2020) - Tan, Yuelong; Chen, Linlin; Li, Siwei; Hao, He; Zhang, Delong
Osteosarcoma is the most common primary malignant bone tumor in the clinic. It is more common in children and adolescents. It has high malignancy, early metastasis rate, rapid disease progression, and high mortality. Although past years have witnessed the great improvement in the treatments of osteosarcoma, there remains a long way to go. MicroRNAs affect the malignant biological behaviors such as tumor proliferation and metastasis by regulating their target genes. In this study, we investigated the role and mechanism of miR-384 in osteosarcoma. Quantitative real-time polymerase chain reaction assay was performed to detect the expression of miR-384 and insulin-like growth factor binding protein 3 in osteosarcoma tissues and cell lines and established its correlation with osteosarcoma tumor progression and metastasis. To probe whether miR-384 played a tumor suppression role in osteosarcoma, we carried out gain-of-function and loss-of-function assays. Cell Counting Kit-8, cell colony formation, and transwell assays were carried out to determine the cells proliferation and invasion, respectively. Western blot was used to detect the changes of epithelial–mesenchymal transition marker proteins and insulin-like growth factor binding protein 3. MiR-384 was downregulated in osteosarcoma tissues and cell lines. MiR-384 was overexpressed in G292 cells transfected with miR-384 mimics and knocked down in Saos-2 cells with small hairpin RNA targeting miR-384. Ectopic expression of miR-384 inhibited osteosarcoma cell proliferation, colony formation, and invasion. E-cadherin was brought to a decrease whereas N-cadherin and Snail to an increase under the silent expression of miR-384, while overexpression of miR-384 led to an opposite result. MiR-384 could regulate insulin-like growth factor binding protein 3 expression in osteosarcoma. Quantitative polymerase chain reaction and Western blotting results validated that miR-384 knockdown downgrades both messenger RNA and protein levels of insulin-like growth factor binding protein 3 in G292 cells, while miR-384 upregulation exerted an opposite effect in Saos-2 cells. Insulin-like growth factor binding protein 3 was upregulated in osteosarcoma tissues and osteosarcoma cell lines compared with normal ones. Through the bioinformatics database found that the upstream transcriptional regulator of insulin-like growth factor binding protein 3 is MECP2. So miR-384 can directly inhibit MECP2 and then promote the expression of insulin-like growth factor binding protein 3. These results suggested that miR-384 might be a potential therapeutic targets and biomarker in osteosarcoma.